Project-Based Learning with Qreatif Educative: Improving Early Writing Skills in Elementary Schools - Lasmidewi, Reni Noviani; Nurjamin, Asep; Hamdani, Agus; Nurwahidah, Lina Siti (Edukasi, 2026)
Beginning writing is a foundational literacy skill in early elementary education because it supports students’ ability to form letters, build words, and construct simple sentences to express ideas. However, classroom instruction at the early writing stage often remains procedural and copy-based, with limited media to stimulate idea development, engagement, and confidence in initiating written texts. This study developed and tested a Project-Based Learning (PjBL) model supported by the interactive digital application Qreatif Educative to improve Grade 1 students’ beginning writing skills. Using a Research and Development (R&D) approach, the study followed sequential stages of needs analysis, information gathering, product design, expert validation, limited trial, field trial, and final revision. The research site was SDN 3 Sukamaju. Validators consisted of two content experts and two media experts. A small-group trial involved 7 students, followed by a field trial involving 16 students. Data were collected through observations, interviews, questionnaires, documentation, and pretest–posttest writing assessments. Qualitative data were analyzed thematically to capture usability feedback and implementation challenges, while quantitative data were analyzed descriptively using feasibility percentages and inferentially using a paired-sample t-test. The developed model and media were rated very feasible by experts, with content and media validation results reaching 88%. Student responses in the small-group trial indicated very positive usability and engagement, with an average feasibility score of 85.56%. Effectiveness testing in the field trial demonstrated a significant improvement in students’ beginning writing performance after implementation (paired-sample t-test, p = .000 < .05). Overall, integrating PjBL with Qreatif Educative provides a feasible and effective approach to strengthening beginning writing through structured projects, interactive practice, and guided feedback in early elementary classrooms.